الواقعية التقدمية في أدب يوسف القعيد: دراسة في رواية الحرب في بر مصر - حمزة، محمود محمد (جامعة الأزهر - کلیة اللغة العربیة بالمنوفیة, 2020)
ليس هناك فارق في أدب يوسف القعيد أنه نصنفه واقعية تقدمية أو واقعية اشتراكية أو واقعية القاع، فكلها تعبيرات تدل على مضمون واحد هو ذلك الهم الاجتماعي لدى هذا النمط من الكتابة بتجسيد هموم الواقع المعاصر، والقرية عند القعيد المعين والزاد، يقلب فيها كيفما شاء حتى صارت (الضهرية) معادلا موضوعيا لتلك الواقعية التقدمية، يقلبها القعيد كيفما أراد من نص إلى نص وفي كل مرة تنبت نباتا جديدا. ولقد حاول القعيد في أعماله الروائية لا سيما في "الحرب في بر مصر" و "يحدث في مصر الآن" أن يقيم علاقة بين المرسل والمتلقي، المبدع والقارئ يجعل فيها القعيد القارئ شريكا في إنتاج النص والإجابة عن الأسئلة اللانهائية، ومثلت ظاهرة (الميتا قص - الميتا سرد - الميتا حكى) أو ما يمكن أن تطلق عليه تعدد الرواة حالة من صراع الذاتيات والذي يجسد صراع الواقع، حيث يعتبر كل راو نفسه طرفا في الصراع، ورواية (الحرب في بر مصر) رفض واضح للواقعية التقليدية واقتراب حقيقي لواقعية التجريب في محاولة جادة لتوضيح الفارق الفني بين رصد الواقع ومحاولة إعادة إنتاجه. وإن الرواة الست (العمدة - المتعهد - الخفير - الصديق - الضابط - المحقق) شكلوا الحدث بدرجات متفاوتة، فكان المتعهد والمحقق أكثرهما قدرة على التعبير عن الحدث بينما بقى العمدة عصب الرواية واكتفي الصديق والضابط أن يكونا ناقلين للأحداث في ظل غياب مقصود للشخصية الرئيسية (مصري).
There is no difference in the literature of Youssef Alkaeed as it is classified as progressive realism, socialist realism, or bottom reality. All of which are expressions indicating one content: social concern of this type of writing embodying the concerns of temporary reality. The village was Alakeed’s main resource. He shaped it as much he wanted until (Al-Dahriyah) became an objective element of this progressive realism. Every time Alakeed shaped it, a new plant started to grow. In his fictional works, especially in “War In The Shore of Egypt” and “Now Happening In Egypt”, he tried to establish a relationship between the sender and the recipient or the creator and the reader. This way he makes the reader a partner in producing the text and answering the endless questions. The phenomenon of meta-narration, or what might be called multiple narrators, is called a state of self-struggle. It embodies the struggle of reality in which each narrator considers himself a party in the conflict. The novel “War In The Shore of Egypt” is also a clear rejection of traditional realism and a real approach to experimentation realism in a sharp attempt to clarify the technical difference between monitoring reality and trying to reproduce it. The sic narrators (Al Omda- Al Mota’ahed- Al Kafeer- Al Sadeek- Al Dabet- Al Mohakek) formed the event in varying degrees. Al Mota’ahed and Al Mohakek were the most able to express the event, while Al Omda remained the nerve of the novel and Al Sadeek and Al Dabet contended themselves to be carriers of the event in light of the intended absence of the main character (Masry).
Keywords: الأدب العربي -- رواية الحرب في بر مصر -- القعيد، يوسف -- النقد الأدبي